The effect of 2000 ıu/day vitamin D supplementation on insulin resistance and cardiovascular risk parameters in vitamin D deficient obese adolescents - Bilici, Meliha Esra; Erdeve, Şenay Savaş; Çetinkaya, Semra; Aycan, Zehra (The Turkish Journal of Pediatrics, 2019)
The aim of this study was to determine the vitamin D deficiency prevalence in obese adolescents and to investigate the effect of vitamin D supplementation on insulin resistance and cardiovascular risk parameters in obese adolescents with vitamin D deficiency. Ninety-six obese adolescents aged 10-18 years were divided in 2 groups according to their vitamin D levels: Deficient group ( < 12ng/ ml) and sufficient group (≥12ng/ml). All patients in the vitamin D deficiency group were recommended 2000IU/day vitamin D supplementation. Fifty four (56.3%) patients had vitamin D deficiency. The only difference between the two groups was PTH level which was higher in the vitamin D deficiency group. Vitamin D reached sufficient levels in 22 (95.6%) out of the 23 patients with the 3 month supplementation of 2000 IU/day vitamin D. There was a significant decrease in weight Standard Deviation Score (SDS), Body Mass Index (BMI) SDS, hip circumference, total cholesterol, LDL, HbA1c, AST, PTH and interleukin-6 while no significant change was seen in measurements of glucose, insulin, HOMA-IR, C-peptide and the rate of metabolic syndrome. There were decreases in levels of total cholesterol and LDL with vitamin D treatment, while there was no significant change in insulin resistance. Vitamin D reduced interleukin-6 levels by its antiinflammatory effect.
Keywords: cardiovasculer risk; insulin resistance; obesity; vitamin D.